PENINGKATKAN HASIL BELAJAR IPAS MATERI CAHAYA DAN SIFATNYA MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA E-MODUL KELAS V SEKOLAH DASAR - Atmojo, Pengkuh Aji; Isdaryanti, Barokah; Wijayati, Nanik; Avrilianda, Decky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the learning outcomes of fifth-grade students at SDN Srondol Wetan 06 in the IPAS subject on the topic of light and its properties through the implementation of the Problem Based Learning (PBL) model assisted by e-module media. The research method used was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects of this study were fifth-grade students of SDN Srondol Wetan 06. The results of the study indicate that the implementation of the PBL model supported by e-modules can improve students’ learning outcomes. The improvement in learning outcomes was significant in each cycle. In the pre-cycle, the average score of students was 63.2 with a mastery percentage of 46.4%. In Cycle I, the average score increased to 78.6 with a mastery percentage of 67.9%. Furthermore, in Cycle II, the average score reached 81.4 with a mastery percentage of 82.1%, which exceeded the Minimum Mastery Criteria (MMC) of 75.Thus, it can be concluded that the implementation of the Problem Based Learning model assisted by e-module media is effective in improving the learning outcomes of fifth-grade students at SDN Srondol Wetan 06 in the IPAS subject on the topic of light and its properties.